THE ROLE OF DIGITAL MEDIA IN MAINTAINING LOCAL CULTURE INDONESIA IN THE ERA OF GLOBALIZATION - Hamdiah, Magfirotul; Ahnaf, Fatih Holis (ASMARALOKA: Jurnal Bidang Pendidikan, Linguistik, dan Sastra Indonesia, 2024)
The era of globalization is marked by advances in information and communication technology that have an impact on the spread of information that can take place quickly and widely, not limited to developed countries with high economic growth, but also across the borders of poor and developing countries with low economic growth. For Indonesia, the influx of western values is a ride on the wave of globalization for Indonesian society which is a threat to the indigenous culture that describes the distinctive locality of the regions in this country. For example, young children may see pornographic images, teenagers who are supposed to be the cultural milestones of a nation that upholds hedonism and modernity. According to Dr. Hench, strategies are needed that actually take advantage of the role of digital media in counteracting negative influences from outside due to globalization, including websites, mobile applications, mobile games, and so on that can be used for the basis of the approach to spreading Indonesian culture through the internet with an emphasis on spreading through blogs and social media, making local media into national and international media capable of increasing the role of local culture in the world arena and finally implementing counter- culture, which is an effort from a local media to stem the influences from outside the media by highlighting the characteristics that come from the local community.outcomes of fourthgrade students of MI Ma'arif Slendro, Sragen Regency.